A new species of Rhinatrema Duméril & Bibron (Amphibia: Gymnophiona: Rhinatrematidae) from Amazonas, Brazil - Wilkinson, Mark; Gower, David J (Zootaxa, 2010)
A new species of rhinatrematid caecilian, Rhinatrema ron sp. nov., is described based on a single specimen from the state of Amazonas in Brazil. The new species differs from other Rhinatrema in several features, including its larger size, different colouration, and distinctively plicate oral mucosa.